Educação, microcrédito e pobreza no brasil: o caráter educativo do microcrédito produtivo orientado – o caso do banco revelação no Ceará - Silva, Clébia Mardônia Freitas (2011)
Education plays an important part in the lives of citizens. In Brazil, in addition to the educational system, there is education applied in non-schooling learning – non-formal or informal education – used by both Government and organized civil society as NGOs, networks, forums, and so forth. It is often articulated with programs, projects and actions for social development, as is the case of production projects intended to contribute to labor and financial integration for the poor through the provision of an oriented productive microcredit. The study aimed to understand what is the educational character of the oriented productive microcredit, when using the community bank as an instrument that intends to operate for inclusion of the poor into the financial system and, consequently, into society. Therefore, it reveals the dynamics of education to contribute to the implementation of public policies. It also intends to characterize the education and the context in which the microcredit fits, emphasizing the inclusion of the poor; understanding what is a community bank; exploring the meaning of education and its relations with the oriented productive microcredit; showing the experience featuring the Revelation bank learning mediated by the subjects, and finally, to explore the meaning of education revealed by the experiences of the Revelation bank subjects. A qualitative study, descriptive and explanatory, grown in the field of education, was carried out with the following theme concepts: poverty and unemployment related to supply and demand of an oriented productive microcredit. A strategic case study is used, based on the experience of the Revelation bank in Ceará, supported by the National Agency of microenterprise development (ANDE), since the year 2003. Based on the analysis and the dialectic method of content analysis defended by Bogdan and Biklen (1994), and the contributions of the concepts of action research and ethnography, although not a true ethnograpy itself. It is based, especially on the concepts of Freire’s pedagogy and Dewey’s understanding, which emphasizes the importance of considering education as an experience. Semi-structured interviews were conducted; participation in meetings and participant observation, using a field journal, tape recorder and camera as the main instruments of data collection. It emphasizes, in terms of the members of the bank Revelation, the meaning of the education employed in the provision of the oriented productive microcredit, as an education that can be liberating, but also regulatory. Depending on the adopted financial conception, whether capitalist or communitarian, the provision of microcredit can reaffirm or contribute to counteract the capitalist system. The participation and solidarity are the key attributes used for the empowerment of individuals.